Hoya rotundiflora (Apocynaceae, Asclepiadoideae), a new horticulturally important species from Myanmar - Rodda, Michele; Simonsson, Nadhanielle (Phytotaxa, 2011)
A new species, Hoya rotundiflora, originally found in a market in Thailand and collected in neighboring Myanmar, is described, illustrated and compared with related species. Hoya rotundiflora appears to be related to Hoya thomsonii and Hoya lyi due to the similar growth habit, but it can be easily distinguished by the shape of leaves, corolla and corona lobes.